TATA KELOLA SISTEM INFORMASI MANAJEMEN PROFIL GURU DAN SISWA SD IT AL HANIF GADINGREJO BERBASIS WEB MOBILE - Gustiara, Meda; Puspitasari, Tuti (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
In the digital era that continues to develop today, the use of information technology is an important aspect in the context of education. SD IT Al Hanif Gadingrejo is required to adopt information technology to improve the management of teacher and student profiles. Teachers and administrative staff are faced with accessibility and mobility challenges. They need easy and fast access to teacher and student profile data, both inside and outside the school environment. The aim of the researchers in this study was to provide the right solution to overcome problems in processing teacher and student data at SD IT Al Hanif. The data collection method in this study is using interviews, observation and literature studies. While the design model used in this study is the waterfall approach as a software engineering method. SD IT Al Hanif Gadingrejo has a total of 85 students consisting of 43 boys and 42 girls. Based on the results of the research and discussion previously described, the authors have designed a system that aims to facilitate the management of teacher profiles, student data, and online registration at SD IT Al Hanif Gadingrejo. After testing the system, it can be concluded that this system runs smoothly according to the expectations set by the author. This system successfully fulfills the need for data management with high efficiency and ease of use. With the implementation of this system, it is hoped that the process of managing teacher profiles, student data and online registration at SD IT Al Hanif Gadingrejo will become more structured, fast and accurate.